2018
DOI: 10.32598/sija.13.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Meaning of Life and Psychological Well-being, in Youth, Adults, and Elderly (A Comparative Study of Three Age Groups)

Abstract: Objectives The present study aimed to examine the meaning in life and well-being of young, middleaged, and older adults. Methods & Materials In this research, a total of 215 participants including 84 young (aged 17-25 years), 59 middle-aged (aged 26-46 years), and 72 older adults (aged 65-80 years) were selected from Tehran city via purposive sampling. The instruments used in this study consisted of the meaning of life questionnaire and Ryffs Scales of Psychological Well-being. Results The results of Mancova a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
2
9
1
Order By: Relevance
“…Our results showed no significant correlation between PWB and PL in male prisoners. These results were not consistent with previous studies ( 24 , 41 ), indicating that PWB was significantly correlated with PL score. One reason why these studies are inconsistent with the present study may be that the studies were conducted on normal groups, while prisoners are vulnerable with special circumstances.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed no significant correlation between PWB and PL in male prisoners. These results were not consistent with previous studies ( 24 , 41 ), indicating that PWB was significantly correlated with PL score. One reason why these studies are inconsistent with the present study may be that the studies were conducted on normal groups, while prisoners are vulnerable with special circumstances.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the present study showed that wisdom has a positive and significant effect on academic vitality through the mediation of academic self-concept. These results are consistent with the results of research by Orang et al (2018);Hassanzadeh, & Vatandoust (2018); Raashidzade et al (2019); Zabihi Hesari (2017) Ghaderiani (2016); Ganji & Soufi (2015) and Grossmann et al (2016) were in line. A wise solution is a balanced solution; in such a way that it considers the conflicting intrapersonal, interpersonal and transcendental interests, in the short and long term, and also incorporates positive moral values in decisionmaking.…”
Section: Discussionsupporting
confidence: 92%
“…These results were not in line with the results of Rostami (2014) and Li et al (2020). Explaining this finding, we can say that self-concept is a combination of thoughts and feelings that it has and the overall evaluation of the individual derives from his personality (Orang, Hashemi Razini, Ramshini Orang, 2018). Internal and external transformational assets are considered as the heart of positive transformation, effective individual and social factors.…”
Section: Discussionmentioning
confidence: 63%
“…Some consider resilience as an intrinsic characteristic of humans to moderate stress and adapt to different conditions (Waller, 2001). Resilience is an important factor in adapting successfully to changes, and enhancing the ability to resist problems that make it possible for individuals to benefit from their adaptive skills and turn stressful situations into an opportunity to learn and grow, and focus on the problem to control their stress (Connor & Davidson, 2003;Orang, Hashemi Razini, & Ramshini, 2018).…”
Section: Introductionmentioning
confidence: 99%